2018
DOI: 10.1002/chem.201705700
|View full text |Cite
|
Sign up to set email alerts
|

Natural Deposition Strategy for Interfacial, Self‐Assembled, Large‐Scale, Densely Packed, Monolayer Film with Ligand‐Exchanged Gold Nanorods for In Situ Surface‐Enhanced Raman Scattering Drug Detection

Abstract: Liquid interfacial self-assembly of metal nanoparticles holds great promise for its various applications, such as in tunable optical devices, plasmonics, sensors, and catalysis. However, the construction of large-area, ordered, anisotropic, nanoparticle monolayers and the acquisition of self-assembled interface films are still significant challenges. Herein, a rapid, validated method to fabricate large-scale, close-packed nanomaterials at the cyclohexane/water interface, in which hydrophilic cetyltrimethylammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 64 publications
0
33
0
1
Order By: Relevance
“…An effective approach to overcome this problem is to use bulky polymeric molecules, such as polyvinylpyrrolidone (PVP), poly(Nisopropylacrylamide) (NIPAM), thiolated poly (ethylene glycol) (SH-PEG) and thiolated polystyrene (SH-PS), as modifiers to provide interparticle steric repulsion to prevent aggregation. [40][41][42][43] For example, Liz-Marzán et al reported a method for the assembly of a wide variety of Au and Ag nanoparticles of different sizes (up to 200 nm) and shapes (including spheres, rods and stars), as shown in Figure 2b. [42] In their work, a combination of PEG-SH and dodecane thiol were used as modifiers, since it was discovered that the use of dodecane thiols alone led to particle aggregation.…”
Section: Section 11 Charge-reduction With Chemical Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective approach to overcome this problem is to use bulky polymeric molecules, such as polyvinylpyrrolidone (PVP), poly(Nisopropylacrylamide) (NIPAM), thiolated poly (ethylene glycol) (SH-PEG) and thiolated polystyrene (SH-PS), as modifiers to provide interparticle steric repulsion to prevent aggregation. [40][41][42][43] For example, Liz-Marzán et al reported a method for the assembly of a wide variety of Au and Ag nanoparticles of different sizes (up to 200 nm) and shapes (including spheres, rods and stars), as shown in Figure 2b. [42] In their work, a combination of PEG-SH and dodecane thiol were used as modifiers, since it was discovered that the use of dodecane thiols alone led to particle aggregation.…”
Section: Section 11 Charge-reduction With Chemical Modifiersmentioning
confidence: 99%
“…[85][86][87][88][89][90] Similarly, it has been shown that arrays can be deposited onto the substrate material by placing the substrate at the bottom of the reaction vessel and then draining away the liquid phases. [40,[91][92] The biggest advantage of the physical deposition strategy lies in its versatility, which allows the nanoparticle arrays to be transferred onto almost any type of solid surface with ease, and the way in which the product material can combine the functionalities of both the 2D arrays and the solid substrates. (Figure 7a).…”
Section: Section 21 Transferring Soft-arrays Onto Rigid-substratesmentioning
confidence: 99%
“…Surprisingly, when a 0.6 μL droplet of 10 −7 M CV solution was placed onto a nanoparticle coated tip and allowed to dry, the resulting deposit did not give a detectable SERS signal, despite the fact that this process produced a deposited layer of dye on the surface which could be observed by SEM and gave a noticeable purple tint to the nanoparticle coated tip (Figures S3 and S4). The origin of this lack of signal was not simply that CV gives low signals with these nanoparticles because we and other research groups have shown that the parent interfacial metal films give very strong SERS enhancement both in situ and as films deposited onto planar substrates, such as a quartz slide [27–34].…”
Section: Resultsmentioning
confidence: 99%
“…与单个金属纳米粒子相比,组装体由于耦合作 用引起电磁场局部增强,形成的拉曼散射强度高达 六个数量级, 具有更高的表面增强拉曼散射 (SERS) [87] ,是强有力的化学和生物传感现象 [88] 。Ma 等 [89] 制备了由金纳米颗粒在环己烷/水界面处自组装形 成的表面增强拉曼平台,用于农药残留量检测。在 环己烷/水双相界面,以亲水性十六烷基三甲基溴化 铵包覆的金纳米棒为自组装基元,形成的二维阵列 能极大地增强 SERS,由此获得的便携式拉曼光谱 仪可以检测人体尿液中极低含量的甲基苯丙胺,为 毒品的快速侦查提供帮助 [90] 。此外还有金纳米粒子 组装胶带,可用于检测鱼表面残留的孔雀石绿 [91] ; 金/银纳米球自组装单分子膜可检测三苯基甲烷染 料 [92] ; 采用银/氧化亚铜自组装纳米复合薄膜制作非 酶电化学 H2O2 传感器 [93] 。 强的 SERS 效应主要集中于 Au [94] 、Ag [95] 和 Cu 等金属 [96][97] ,但这些金属材料成本较高,且稳定性 不理想 [98] ,生物相容性差 [99] ,急需替代 SERS 的材 料 [100] 。 Lan 等 [101] 报道了基于石墨烯量子点和 Mn3O4 的自组装复合材料,具有较好的 SERS 效应。Yi 等 [102] 开发了基于紧密堆积的 SiO2 球形颗粒实现 SERS 的技术,在表面化学、生物学和微电子学等 领域都有潜在的应用。除传统材料外,新型二维层 状材料 MXene [103] 同样可以用于 SERS。Chen 等 [104] 研究了磺胺酸改性 MXene,表明的其潜在 SERS 应 用价值。…”
Section: 表面增强拉曼散射unclassified